Self-Assessment of Non-communicable Diseases related Competencies among Interns of a Medical Institute of Nepal - Pradhan, Pranil MS; Adhikari, Bidur; Pant, Sagun B; Ranjit, Nirju; Rawal, Suniti; Basnet, Sudha (Journal of Institute of Medicine Nepal, 2022)
Introduction: One of the essential strategies to tackle rising burden of non- communicable diseases (NCD) is development of competent local human resource. Assessing the level of competencies in pre-service curriculum is the first step towards building an NCD-ready health workforce. This study aimed to assess perception of competence in delivering World Health Organization Package of Essential Non- communicable diseases (WHO-PEN) interventions among interns of Maharajgunj Medical Campus of Institute of Medicine (IOM). Methods: A survey was conducted at Maharajgunj Medical Campus of Institute of Medicine among interns using online questionnaire. The questionnaire contained seven sections on different competencies to prevent and manage NCDs. Ethical approval was obtained from Institutional Review Committee of IOM. Descriptive analysis was done to identify the level of competencies. Statistical analysis was performed using Microsoft Excel and IBM SPSS version 20. Results: Majority of the interns expressed low to moderate confidence in managing patients with presenting complaints of major NCDs. Most interns could perform diagnostic procedures and screening related to NCDs and mental disorders under supervision only (56.9%-68.6%), and one third felt they were unable to perform spirometry and visual inspection of cervix with acetic acid. Most interns could provide counseling on major NCD risk factors, self-care and palliative care only under supervision. Majority could not identify key NCD service performance measures and their data sources. Conclusion: Skills of independently diagnosing and screening for NCDs, counselling on healthy lifestyle, alcohol and tobacco cessation and conduct motivational interviewing, self-care and palliative care were limited.